2016
DOI: 10.1109/tifs.2016.2569061
|View full text |Cite
|
Sign up to set email alerts
|

Discriminant Correlation Analysis: Real-Time Feature Level Fusion for Multimodal Biometric Recognition

Abstract: Information fusion is a key step in multimodal biometric systems. Fusion of information can occur at different levels of a recognition system, i.e., at the feature level, matching-score level, or decision level. However, feature level fusion is believed to be more effective owing to the fact that a feature set contains richer information about the input biometric data than the matching score or the output decision of a classifier. The goal of feature fusion for recognition is to combine relevant information fr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
181
0
3

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 329 publications
(184 citation statements)
references
References 51 publications
0
181
0
3
Order By: Relevance
“…The feature level fusion techniques include the serial feature fusion [17], the parallel feature fusion [18], the CCAbased feature fusion [19], JSRC [14], SMDL [20] and DCA/MDCA [16] algorithms. Note that in case of more than two modalities, the parallel feature fusion method cannot be applied.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The feature level fusion techniques include the serial feature fusion [17], the parallel feature fusion [18], the CCAbased feature fusion [19], JSRC [14], SMDL [20] and DCA/MDCA [16] algorithms. Note that in case of more than two modalities, the parallel feature fusion method cannot be applied.…”
Section: Resultsmentioning
confidence: 99%
“…Compared to score, rank, and decision level fusions, feature level fusion results in a better discriminative classifier [12], [13], due to preservation of raw information [14]. The feature level fusion integrates different features extracted from different modalities into a more abstract and compact feature representation, which can be further used for classification, ver-ification, or identification [15], [16]. Recently several authors have exploited feature level fusion for multimodal biometric identification.…”
Section: Introductionmentioning
confidence: 99%
“…В частности, когда классы объектов, подлежащих изучению, долж-ным образом определены и описаны, эта проблема сводится к выбору того из имеющихся классов, к которому должен быть отнесен вновь обнару-женный объект, и получила название дискрими-нантного анализа, методы которого сегодня ак-тивно развиваются (см. [3]). Одно из востребо-ванных применений этого аппарата -задачи так называемой доказательной медицины, основы ко-торой изложены в [4,5].…”
Section: Doi 1014258/izvasu(2017)4-15unclassified
“…Haghighat et al [2] reported that feature level fusion can be more effective in terms of biometric data classification by owing to that a feature set which contains richer information in regard the input biometric data than that of matching score or decision level fusion. They proposed a discriminant correlation analysis (DCA), a new technique of feature level fusion that integrates the class associations into the correlation analysis of the feature sets.…”
Section: Multimodal Biometric Recognition Systemsmentioning
confidence: 99%